Climate Change in the Arctic - A Hot Topic. SWIPA 2011: Snow, Water, Ice and Permafrost in the Arctic. - Arctic Monitoring and Assessment Programme (AMAP) (Arctic Monitoring and Assessment Programme (AMAP), 2012)
Educational use: This report (in part or in its entirety) and other SWIPA products available from www.amap.no can be used freely as teaching materials and for other educational purposes. The only condition of such use is acknowledgement of AMAP/SWIPA as the source of the material according to the recommended citation. In the case of questions regarding educational use, please contact the AMAP Secretariat (amap@amap.no). Note: This report contains images (e.g. photographs) for which permission for use will need to be obtained from original copyright holders (see above).